Three new species of the thorid shrimp genus Lebbeus White, 1847 (Decapoda: Caridea) from Nemuro Strait, Hokkaido, Japan, with supplemental note on L. fujimotoi Matsuzaki, Hibino & Komai, 2015 - Komai, Tomoyuki; Matsuzaki, Koji (Zootaxa, 2022)
Based on a collection of deep-water caridean shrimps captured by commercial baited traps and gill nets operated in Nemuro Strait, southwestern part of the Sea of Okhotsk, three new species of the thorid shrimp genus Lebbeus White, 1847, L. rufomaculosus n. sp., L. subtilis n. sp. and L. tenuipes n. sp., are described and illustrated. Integrative approach using morphological comparison and genetic analyses with the mitochondrial COI and 16S rRNA genes is taken to clarify specific identities of those newly recognized taxa. In addition, an aberrant male specimen of L. fujimotoi Matsuzaki, Hibino & Komai, 2015 is reported, of which the identity is confirmed by genetic analyses.